One day on our blue planet ... in the ocean - Bailey, Ella (Bailey, Ella. One day on our blue planet., 2018)
"The series focused on the way our young animal friends spend a day continues with an adventurous dolphin calf, as she explores the vast Pacific ocean with her mother and meets the many wonderful water dwelling creatures that live there.